ADMINISTRATIVE REFORMS - AS A FACTOR OF MODERNIZATION - Mukhimjon Khirgizboev (Western European Studies, 2025)
The article analyzes the processes of modernizing and decentralizing government administration bodies in the Republic of Uzbekistan. These processes are rooted in the state governance model proposed by President Shavkat Mirziyoyev, which aims to bring public services closer to the people and focuses on the development of civil society and democratic values. The importance of administrative reforms in Uzbekistan and the factors driving them are examined in detail. Additionally, the experience of decentralization in Western countries is studied through a comparative approach. The article explores the political, administrative, and fiscal forms of decentralization and their significance in Uzbekistan's administrative reforms.
Keywords: Uzbekistan; administrative reforms; public administration; decentralization